Pengaruh Globalisasi Terhadap Eksistensi Identitas Nasional Bangsa Indonesia Saat Ini - Annisa Azzahra Julianty (Institut Agama Islam Negeri Ponorogo, 2022)
National identity is a matter of vital importance in a country. Without an identity, a country is unrecognized in the eyes of the world. National identity is defined asa dynamic condition formed by various factors, such as ethnicity, culture, language, religion, ideology, and so on. The dynamics of national identity can be affected by the current globalization. Globalization is defined as the world's freedom to develop different aspects of life, such as technology, science, culture, and so on. This process is being propagated by technologies and information controlled by developed countries. Thus, Indonesia as a developing country has more influence than influence. Globalization influences both positive and negative. The positive effects of globalization can be harnessed in the development of nations. The negative effects of globalization, however, could remove the national identity of nations. Therefore, it takes effort to strengthen nation's identity by liberating the negative effects of globalization that can have a powerful impact on the social order, and education plays a key role in growing a superior personality for the next generation.